Massive haemorrhagic pericardial effusion as the cardiac manifestation of Salmonella enteritidis infection in a severely immunocompromised patient - Ho, Yik Hon; Caryn Tsujean, Lim; Ling, Hwei Sung; Thung, Su Fui; Chua, Hock Hin; Ong, Tiong Kiam (Malaysia Medical Association, 2023)
A 41-years-old gentleman was admitted for reduced effort tolerance with non-specific symptoms of weight loss and generalised body weakness. Chest X-ray (CXR) showed cardiomegaly. Echocardiography showed a large pericardial effusion with septation. Emergency pericardiocentesis was performed and pericardial fluid culture grew Salmonella enteritidis (S. enteritidis). He tested positive for the retroviral disease, with a CD4 count of 10 cells/µL. Intravenous (IV) ceftriaxone was administered. A pericardial drain was inserted due to the rapid re-accumulation of pericardial fluid after the initial pericardiocentesis. He also had drainage of his left pleural effusion. He had a guidewire exchange of pericardial drain around 2 weeks after admission, with flushing performed whenever the flow was poor. A repeat echocardiogram showed early signs of constrictive pericarditis with residual pericardial effusion in which intrapericardial fibrinolysis was considered. He was started on antiretroviral therapy (ART) and his condition remained stable. The pericardial drain was kept throughout his admission. Unfortunately, he developed severe sepsis and succumbed to it about a month post-admission.